2015
DOI: 10.1080/15476286.2015.1018502
|View full text |Cite
|
Sign up to set email alerts
|

Domain movements during CCA-addition: A new function for motif C in the catalytic core of the human tRNA nucleotidyltransferases

Abstract: These authors equally contributed to this work.Keywords: CCA-adding enzyme, CCA-addition, DEER, EPR spectroscopy, tRNA nucleotidyltransferase, tRNA, tRNA maturation CCA-adding enzymes are highly specific RNA polymerases that synthesize and maintain the sequence CCA at the tRNA 3 0 -end. This nucleotide triplet is a prerequisite for tRNAs to be aminoacylated and to participate in protein biosynthesis. During CCA-addition, a set of highly conserved motifs in the catalytic core of these enzymes is responsible for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(43 citation statements)
references
References 44 publications
2
41
0
Order By: Relevance
“…As controls, wt enzymes HsaCCA and RcuCCA were included. The Romanomermis enzyme showed an efficient and robust binding to mt-tRNA Ile , resulting in a K d value of 0.9 µM, while for the human enzyme, no significant binding could be detected, as previously reported for this enzyme class (Shi et al, 1998;Tretbar et al, 2011;Ernst et al, 2015). With K d values of 1.5 and 1.4 µM, both Hsa/Rcu chimeras A and B show a binding behavior similar to that of the RcuCCA wild type enzyme, demonstrating that both N-and C-termini contribute to the recognition of armless tRNAs.…”
Section: Rcucca Adds a Complete Cca-triplet To Armless And Canonical supporting
confidence: 79%
See 2 more Smart Citations
“…As controls, wt enzymes HsaCCA and RcuCCA were included. The Romanomermis enzyme showed an efficient and robust binding to mt-tRNA Ile , resulting in a K d value of 0.9 µM, while for the human enzyme, no significant binding could be detected, as previously reported for this enzyme class (Shi et al, 1998;Tretbar et al, 2011;Ernst et al, 2015). With K d values of 1.5 and 1.4 µM, both Hsa/Rcu chimeras A and B show a binding behavior similar to that of the RcuCCA wild type enzyme, demonstrating that both N-and C-termini contribute to the recognition of armless tRNAs.…”
Section: Rcucca Adds a Complete Cca-triplet To Armless And Canonical supporting
confidence: 79%
“…As EcoCCA showed no activity on armless tRNAs, this enzyme was excluded from further analysis. To discriminate between C-and A-addition, assays were performed on tRNAs lacking the CCA-end in the presence of either α-32 P-CTP or α-32 P-ATP and unlabeled CTP (Lizano et al, 2008;Just et al, 2008;Ernst et al, 2015). As shown in table 1, k cat for CC-addition on tRNA Phe is in a similar range for both enzymes, whereas the incorporation of the terminal A residue is somewhat less efficient for RcuCCA (2-fold).…”
Section: Rcucca Adds a Complete Cca-triplet To Armless And Canonical mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, this is true for both class I ( A. fulgidus ) as well as class II ( Homo sapiens ) CCA‐adding enzymes, indicating that both versions fulfill this scrutinizing function of tRNA stability. In addition, Ernst et al recently observed a similar contraction reaction in the human CCA‐adding enzyme during addition of the terminal A residue, a further indication that class II enzymes follow comparable mechanism to monitor the structural quality of the tRNA substrate . Hence, this inspection of tRNA intactness seems to represent a general quality surveillance in all kingdoms of life.…”
Section: Cca‐adding Enzymes Scrutinize the Structural Stability Of Trnasmentioning
confidence: 80%
“…Hence, it is possible that other enzyme parts important for A-addition are also affected in the CC-adding enzymes. Besides the B/A motif and the flexible loop, a springy hinge region consisting of interacting α-helical elements located in motif C helps to define the number of nucleotides to be incorporated and contributes to the structural rearrangements of the NTP binding pocket, although no direct interaction with the loop region could be demonstrated [24,33,58]. As the sequence variation of this motif between CC-and CCA-adding enzymes is identical to that found within the CCA-adding enzymes, it is highly unlikely that motif C mutations are responsible for the restricted activity of the investigated CC-adding enzymes.…”
Section: The Flexible Loop-equally Important For the Evolution Of Cc-mentioning
confidence: 99%